1992
DOI: 10.1111/j.1751-1097.1992.tb04257.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Behind the Resistance of Spheroids to Photodynamic Treatment: A Flow Cytometry Study

Abstract: The influence of cell heterogeneity on response to photodynamic treatment (PDT) has been investigated using the human colon adenocarcinoma line WiDr, grown as spheroids and exposed to hematoporphyrin derivative. The spheroids show a marked spheroid size-dependent resistance to PDT. Using a flow cytometer, cell sub-populations have been separated, on the basis of drug fluorescence, from single cell suspensions prepared from 500 microm diameter spheroids. Cells low in fluorescence have been shown to be resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
1
9
0
1
Order By: Relevance
“…23 However, the heterogeneity of PS uptake has been demonstrated in various in vitro and in vivo models. 24,25 The mechanisms of resistance to PDT ascribed to the PS may be shared with the general mechanisms of MDR, and are related to altered PS uptake and e®lux rates or altered intracellular tra±cking within cancer cells. 26 …”
Section: Interaction Of Mdr and Psmentioning
confidence: 99%
“…23 However, the heterogeneity of PS uptake has been demonstrated in various in vitro and in vivo models. 24,25 The mechanisms of resistance to PDT ascribed to the PS may be shared with the general mechanisms of MDR, and are related to altered PS uptake and e®lux rates or altered intracellular tra±cking within cancer cells. 26 …”
Section: Interaction Of Mdr and Psmentioning
confidence: 99%
“…7,17 Tumor size heterogeneity can play a critical role in the establishment of differential gradients within the tumor microenvironment, such as hypoxia, pH, nutrients, growth factors, cytokines, waste products, and metabolic stress, and consequently their responses to drug treatment. 18 Thus, there is an unmet need for methods to generate sufficient tumor aggregates of controlled sizes so that they can be utilized for preclinical cancer drug efficacy screening. Emerging microfabrication and micromolding techniques 19 offer an opportunity to control the size of 3D tissue constructs more efficiently.…”
mentioning
confidence: 99%
“…40 Some studies suggest that cells which are resistant to PDT have reduced LDL uptake. 38 Another explanation may be that the Photosan-3 TM penetrates the spheroids poorly, leading the inner core of the spheroids relatively free for HpD. However, other spheroid studies have demonstrated the presence of HpD in the spheroid centre after 24 h of drug exposure.…”
Section: Discussionmentioning
confidence: 99%
“…These cells have been shown to be more resistant to PDT than cycling cells. 38 Quiescent cells may undergo many changes with loss of surface microvilli, decrease in uidity and inhibition of phagocytosis leading to a reduction in the permeability and transport of molecules. 39 There is evidence that the low-density lipoprotein (LDL) pathway is important for photosensitizer uptake into cells.…”
Section: Discussionmentioning
confidence: 99%